Developmental regulatory genes in recalcitrant forest trees: advances in somatic regeneration and genetic transformation - Wang, Ying; Wang, Jing-han; Guo, Pu-rui; Peng, Jing; Xie, Chun-ze; Shi, Yi-dan; Wu, Yuan-hang; Liao, De-zhi; Sheng, Song (Frontiers in Plant Science, 2025)
Forests play a pivotal role in maintaining global ecological balance, supporting economic development, and mitigating climate change. However, many economically and ecologically important tree species—particularly long-lived, highly heterozygous, and genomically complex taxa—remain notoriously recalcitrant to efficient clonal propagation and genetic transformation. Major constraints include low somatic regeneration capacity, strong genotype dependence, and limited regeneration of transgenic tissues, all of which impede rapid breeding and practical deployment. In recent years, developmental regulatory genes (DEV genes), which govern cell fate reprogramming and facilitate regeneration, have emerged as key molecular targets for overcoming these technical bottlenecks. This review provides a comprehensive synthesis of recent advances in the identification and functional characterization of DEV genes in model systems and crop species, with an emphasis on their translational potential in recalcitrant forest trees. We highlight strategies for leveraging DEV-mediated regulatory mechanisms to enhance somatic regeneration and transformation efficiency, and propose tailored application frameworks for forestry species. Ultimately, the integration of DEV gene-based approaches may offer a robust theoretical and technological foundation for the accelerated breeding, large-scale propagation, and germplasm conservation of elite forest genotypes, thereby contributing to the long-term sustainability of forest ecosystems.